Distribution Pattern of Sand Dollar (Arachnoides placenta) in the Intertidal Ecosystem of Duta Coastal, Probolinggo Regency - Setiawan, Rendy; Amalia, Rizqy; Fajariyah, Susantin; Kurniawan, Joko (Buletin Oseanografi Marina, 2024)
Species Arachnoides placenta can be found in tropical waters, one of which is in the intertidal ecosystem in Duta Coastal. Substrate types at Duta Coastal are dominated by sand and silt substrates and a small portion of muddy sand substrate. The various types of substrates at Duta Coastal are thought to be causing the population A. placenta choose a suitable habitat for their life, so that it can affect the pattern of distribution and density of A. placenta. This research aims to determine the distribution pattern and density of A. placenta in the intertidal ecosystem in Duta Coastal. This study used the method of systematic transect plots. Plots measuring 1x1 m were placed on the transects with a distance between plots of 10 meters. The number of plots laid was 332 plots. The results show the number of individuals A. placenta in the Duta Coastal intertidal ecosystem 828 individuals. The population of the A. placenta species in the Duta Coastal intertidal ecosystem is quite large because the type of substrate is suitable for the life of A. placenta Morisita Index value for the distribution pattern A. placenta is 9.3. Distribution pattern A. placenta in the Duta Beach intertidal ecosystem classified as aggregated and density values A. placenta in the intertidal ecosystem in Duta Coastal is 2.5 ind/m2.